Evaluation of planetary boundary layer schemes on the urban heat islands in the urban agglomeration over the greater bay area in South China - Huang, Ling; Bai, Lanqiang (Frontiers in Earth Science, 2023)
Urbanization of large cities exerts significant changes in surface air temperature, which subsequently lead to inadvertent local weather and climate changes. The exchanges of momentum, moisture and heat within the planetary boundary layer (PBL) impact the urban atmosphere representation. As the first step to gaining a better forecast of urban climates, the sensitivity of the urban environment to seven PBL parameterization schemes (YSU, MRF, ACM2, BL, MYNN, UW and GBM) is evaluated over the Greater Bay Area, South China, during April–June 2018. The performances of these PBL schemes in reproducing the urban environments, including surface air temperature and humidity, temperature profile, urban heat island (UHI), and PBL height, are evaluated against observations from in situ weather stations and radiosondes. The results show a cool/moist bias near the surface during nighttime and a warm/dry bias during daytime for all PBL schemes. The daytime bias is more significant on weak-UHI days, and the nocturnal bias is more significant on strong-UHI days. The “best” scheme is dependent on the exact variables, daily cycles and thermodynamic conditions that are evaluated. Specifically, the MYNN and MRF schemes perform best for daytime and nighttime surface air temperatures, respectively. The MRF scheme also presents the best performance in simulating the observed UHI, with a phase resembling that of the observed diurnal variation. Despite being useful to define the most appropriate setup for urban modeling over South China, this study may serve as a reference for future mesoscale meteorological modeling applications.